Increased Cytotoxic T-Lymphocyte Epitope Variant Cross-Recognition and Functional Avidity Are Associated with Hepatitis C Virus Clearance - Yerly, Daniel; Heckerman, David; Allen, Todd M.; III, John V. Chisholm; Faircloth, Kellie; Linde, Caitlyn H.; Frahm, Nicole; Timm, Joerg; Pichler, Werner J.; Cerny, Andreas; Brander, Christian (Journal of Virology, 2007)
Hepatitis C virus (HCV) clearance has been associated with reduced viral evolution in targeted cytotoxic T-lymphocyte (CTL) epitopes, suggesting that HCV clearers may mount CTL responses with a superior ability to recognize epitope variants and prevent viral immune escape. Here, 40 HCV-infected subjects were tested with 406 10-mer peptides covering the vast majority of the sequence diversity spanning a 197-residue region of the NS3 protein. HCV clearers mounted significantly broader CTL responses of higher functional avidity and with wider variant cross-recognition capacity than nonclearers. These observations have important implications for vaccine approaches that may need to induce high-avidity responses in vivo.